How conscious are adolescent boys about their body image? - Patidar, Ritesh; Verma, Yogendra Singh; Gaur, Ajay (International Journal of Contemporary Pediatrics, 2019)
Background: Perceived body image is an important determinant of nutritional status of adolescent boys. Body image misconception during adolescence is mostly unexplored field in Indian boys. The objective of this study is to assess the perceived body image and degree of dissatisfaction about it, among adolescent boys of different socioeconomic class. Methods: This multistage observational study was conducted on 200 adolescent boys of Gwalior in two different schools. Anthropometric measurements were taken. Information about socioeconomic status and perceived body image, desired body size and actual body size was collected with predesigned questionnaire. Results: Out of 200 study subjects 155 had normal BMI and 36 had high BMI, remaining were thin. Majority of adolescents (90%) desires to be neither thin nor fat and 10% (20) studied adolescent boys desires thin body. Lesser number of study subjects (63, 31.5%) adolescent boys were satisfied with their perceived body image. Satisfaction was more (34.65%) in middle adolescent age group as compared to late adolescent (28.28%). Almost two third (137, 68.6%) adolescent boys were dissatisfied with their perceived body image. Majority of adolescent boys (160, 80%) correctly estimated their body image, only 03% adolescent boys overestimated their body image whereas 17% adolescent boys underestimated their body image. Conclusions: Majority of adolescent boys are dissatisfied with their body image and almost all of them desire to have perfect body size.